Parallel imaging with nonlinear reconstruction using variational penalties - Knoll, Florian; Clason, Christian; Bredies, Kristian; Uecker, Martin; Stollberger, Rudolf (Magnetic Resonance in Medicine, 2012)
A new approach based on nonlinear inversion for autocalibrated parallel imaging with arbitrary sampling patterns is presented. By extending the iteratively regularized Gauss-Newton method with variational penalties, the improved reconstruction quality obtained from joint estimation of image and coil sensitivities is combined with the superior noise suppression of total variation and total generalized variation regularization. In addition, the proposed approach can lead to enhanced removal of sampling artifacts arising from pseudorandom and radial sampling patterns. This is demonstrated for phantom and in vivo measurements. Copyright © 2011 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2021-08-17
Keywords: nonlinear inversion; parallel imaging; pseudorandom sampling; radial sampling; total generalized variation; total variation